Companion piece : a novel - Smith, Ali, 1962- (Pantheon Books, 2022)
"From the Man Booker Prize shortlisted-author of the brilliant Seasonal Quartet series-a major new novel that promises to capture the present moment with Ali Smith's genius and bold spirit. "A story is never an answer. A story is always a question." Here we are in extraordinary times. Is this history? What happens when we cease to trust governments, the media, each other? What have we lost? What stays with us? What does it take to unlock our future? Following her astonishing Seasonal Quartet, Ali Smith again lights a way for us through the nightmarish now, in a vital celebration of companionship in all its timeless and contemporary, legendary and unpindownable, spellbinding and shapeshifting forms. Companion Piece stands apart from the Quartet, which remains discrete unto itself. But like Smith's groundbreaking series, this new novel boldly captures the spirit of the times. "Every hello, like every voice, holds its story ready, waiting.""--